PROSPEK PENGEMBANGAN TANAMAN JAGUNG HIBRIDA PADA LAHAN TADAH HUJAN DI KECAMATAN BONTOTIRO KABUPATEN BULUKUMBA: Prospect of Hybrid Corn Plant Development In rainfed rice fields In Bontotiro District, Bulukumba Regency - Fajri Fajri; Zulkifli Zulkifli; Mohammad Anwar Sadat (Jurnal Agribis, 2019)
Study was conducted in Bontotiro Subdistrict, Bulukumba Regency. This location was chosen with the consideration that have been managing. hybrid corn plants The data used there are two namely: primary data that is the data collected from the observation through a live interview and also through the help of a list of the questionnaire and secondary data that is the data collected from the institutions related or associated with this research.The purpose of this research is knowing the prospect of the development of hybrid corn plants to land in Bontotiro Subdistrict, rain fed Bulukumba Regency. Data were collected from the survey using a questionnaire and with additional observation/observation. Field the data has been accumulating then In tabulation to get real data-data used for purposes of analysis. This study using a method of swot analysis to figure out the prospect of the development of hybrid corn plants to land in Bontotiro Subdistrict, rain fed, Bulukumba regency and the results of research carried out in the prospect of the development of hybrid corn plants to land in kecamatan bontotiro, rain fed Bulukumba Regency are on the quadrant I (one). This quadrant describe a situation which is very profitable for farmers to develop the farming because it has and opportunities so it can take advantage of existing peluang-peluang, as well as using alternative strategy WT.